La fera, il delfino e altre note di onomastica ... - Venuto, Pierino (Università Ca’ Foscari Venezia, Italia, 2016)
This paper aims to plunge into the onomatological world of Horcynus Orca , a novel published in 1975 by Mondadori, created by the epic and deforming genius of the Sicilian (Fortunato) Stefano D’Arrigo (1919-1992). The episode between the Venetian ensign Monanin and the Sicilian fishermen Crocitto and ’Ndria Cambria (who is the main character of the novel) elucidates the difference between name and thing, signifier and significance, imposed word and reality. Starting from the two common names of a unique and ambivalent marine animal – the Sicilian ‘fera’ and the Italian ‘delfino’ – the paper tries to penetrate the expressionistic poetic world of Horcynus and to analyse the powerful and layered language processing: here the names are consequences of the facts; they are emblems of the ‘saw it with my own eyes’ and not of the ‘hearsay’. Therefore, it can hardly happen that ‘fera’ could be undermined by ‘delfino’ in the mind of a fisherman: «the name of an abstract thing, or rather, the abstract name ... : Studi e ricerche ...